Jaminan Sosial Dalam Perspektif Ilmu Ekonomi Islam - Saiful Bahri (IQTISHADUNA: Jurnal Ilmiah Ekonomi Kita, 2012)
Social insurance and social assurance are other names of social security. This course focuses and describes how social security concept in Islam. By exploration history of Prophet Muhammad period and his friend (shahabah) wisdom, this study yet could answer this concept, social security in Islam. Finally, this study will compare the concept of social security in Islam and the capitalist system.